Fanning the Flames of Passion: A Develop Mindset Predicts Strategy-Use Intentions to Cultivate Passion - Chen, Patricia; Lin, Yuching; Pereira, Don J. H.; O’Keefe, Paul A.; Yates, J. Frank (Frontiers in Psychology, 2021)
College students are encouraged to major in subjects they are passionate about, but less often advised about what to do when passion is low. What self-regulatory strategies do students use to up-regulate their passion toward their subjects, and how might they be oriented toward using such effective strategies? Three studies examined how the belief that passion is developed—a “develop” mindset—relates to students’ intentions to use strategies to actively grow their passion. The more strongly students endorsed a develop mindset, the more of these “cultivation strategies” they reported using, and in turn, the larger their increase in reported passion toward their subject majors (Study 1). Instilling a develop mindset causally increased students’ intentions to use more cultivation strategies (Study 2)—with some effects lasting up to a year (Study 3). Instilling a develop mindset can potentially help students to ignite their passion when its flame burns low.